Particle size and preloading pressure Relationship on the consolidation properties of peat soil - Johari, Nurul Nadia (2021)
This study was done to establish the consolidation properties of reconstituted peat with different soil particle sizes and preloading pressures. The determination of soil properties is very important before started any construction work on soil, especially when it involves with peaty soil. Peat is generally known as problematic soil due to high organic matter and have experienced high compressibility (compression index in the range of 0.9 - 1.5), high moisture content (>100%), low soil bearing capacity (5 – 20 kPa) and high void ratio (5 - 15). Thus, several studies have to be done to gain some information on the properties of peat soil since it has special characteristics. Hence, reconstituted samples of selected particles size of peat with different preloading pressures has been used in determining the relationship between soil properties and soil compressibility. The findings were based on experimental investigation, which involved in determining the basic soil properties of peat and the consolidation properties using oedometer tests. The Parit Nipah Darat peat has a liquid limit of 322% with a natural moisture content of 640%. The fiber content and organic content were 61.4% and 83% where has been classified as hemic peat. Based on these findings, the compression index, Cc and swelling index, Cs of Parit Nipah Darat peat for reconstituted sample with preloading pressure of 25kPa, 50kPa and 100kPa were in range of 1.67 to 2.44 and 0.15 to 0.4. However, the preloading pressure applied during reconstitution process does not affect the maximum past pressure of the soil sample and based on the e-log graph